2020
DOI: 10.1177/2325967120960414
|View full text |Cite
|
Sign up to set email alerts
|

Preparation Methods and Clinical Outcomes of Platelet-Rich Plasma for Intra-articular Hip Disorders: A Systematic Review and Meta-analysis of Randomized Clinical Trials

Abstract: Background: Despite its increasing use in the management of musculoskeletal conditions, questions remain regarding the preparation methods of platelet-rich plasma (PRP) and its clinical applications for intra-articular hip disorders, including femoroacetabular impingement syndrome (FAIS), labral pathology, and osteoarthritis (OA). Purpose: To systematically review and assess the preparation methods and clinical outcomes from randomized clinical trials (RCTs) on the use of PRP for intra-articular hip disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…The description of surgical technique was not adequately reported in some studies, which represents a further limitation. Heterogeneity in PRP preparation and processing protocols was evident, as were between-study differences with regard to the initial whole blood volume and centrifugation rate and duration [ 62 65 ]. Battaglia et al.…”
Section: Discussionmentioning
confidence: 99%
“…The description of surgical technique was not adequately reported in some studies, which represents a further limitation. Heterogeneity in PRP preparation and processing protocols was evident, as were between-study differences with regard to the initial whole blood volume and centrifugation rate and duration [ 62 65 ]. Battaglia et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis by Garcia et al in 2020, 7 studies regarding the role of PRP on hip disorders (femoroacetabular impingement syndrome (FAIS), labral pathology, and OA) were assessed (31). Among the four studies evaluating PRP in HIP OA, the most important nding was not seeing any statistically signi cant difference between HA, PRP, and PRP + HA in hip OA treatment after one year.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age and higher OA stages affecting study results, the difference in the PRP preparation protocol and its contents, and the number of PRP injections have all shown to play a role in the results and ndings, which has also been one of the challenges in meta-analyses (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of PRP injection alone in patients with hip OA indicated overall improvements in the majority of albeit, limited trials, Ref. [35] whilst most recently, Kraeutler et al [36] compared Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores and hip flexion from 33 patients treated with either leukocytepoor PRP (LP-PRP) or low molecular weight HA, finding significant improvements up to 12 months after injection, only in the PRP-treated individuals. From a biological perspective, LP-PRP has the capacity to release notable quantities of anti-inflammatory and pro-reparative factors from the platelet granules and in addition, has been previously shown to stimulate HA production in vitro in patient-derived synovitis [37].…”
Section: Discussionmentioning
confidence: 99%